Pengaruh Twitter Sentiment, Reputasi Underwriter, dan Karakteristik Perusahaan terhadap Underpricing IPO: Studi Empiris pada Perusahaan IPO di Bursa Efek Indonesia Periode 2023–2025 - Hafiz Putra Kiyoma; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Twitter sentiment, underwriter reputation, and firm characteristics on IPO underpricing in companies listed on the Indonesia Stock Exchange during the 2023–2025 period. Firm characteristics in this study are proxied by firm age, firm size, and profitability. This research is based on the Efficient Market Hypothesis, which explains that stock prices reflect the information available in the market. This study uses a quantitative approach with secondary data obtained from Refinitiv Terminal, Twitter, and company prospectuses. The sample was selected using purposive sampling, resulting in 143 IPO companies that met the research criteria. Twitter sentiment was measured using a lexicon-based sentiment analysis approach, while underpricing was measured based on the difference between the first-day closing price and the offering price. The data were analyzed using multiple linear regression with SPSS.The results show that Twitter sentiment has a negative and significant effect on IPO underpricing. This finding indicates that higher positive sentiment on Twitter tends to reduce the level of underpricing, as information circulating on social media may help investors assess IPO companies more objectively and support market efficiency in reflecting public information. Meanwhile, underwriter reputation has a negative but insignificant effect on underpricing. Firm age, firm size, and profitability have positive but insignificant effects on underpricing. Simultaneously, Twitter sentiment, underwriter reputation, and firm characteristics have a significant effect on IPO underpricing.